Catalytic ozonation of dibutyl phthalate in the presence of Ag-doped NiFe2O4 and its mechanism. Issue 28 (19th December 2021) - Zheng, Di; Cao, Jiashun; Wang, Peifang; Zhao, Junyu; Zhao, Yujie; Zhang, Teng; Li, Chao
ABSTRACT: In this study, NiFe2 O4 and Ag0.1 Ni0.95 Fe2 O4 were successfully prepared by the sol–gel method and applied to catalyze ozone for dibutyl phthalate (DBP) degrading. The synthesized catalysts were characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, and vibrating sample magnetometer. The removal efficiency was compared with different catalyst dosage, pH condition, and initial DBP concentration for the two catalysts. The results showed that the introduction of Ag0.1 Ni0.95 Fe2 O4 enhanced the ozone decomposition and the utilization efficiency of ozone from 32.2% (ozone alone) to 56.5% and improved the degradation efficiency of DBP significantly. The two catalysts both presented good recycling performance. Furthermore, the scavenger test displayed DBP degradation by catalytic ozonation dominated by OH in this study. These insights into the catalytic ozonation mechanism on Ag0.1 Ni0.95 Fe2 O4 will advance their practical application to the catalytic degradation of organic pollutants. GRAPHICAL ABSTRACT: UF0001